Study of endothelial function in pregnant women with gestational diabetes mellitus by flow mediated dilation of brachial artery - Pandey, Nidhi; Goel, Poonam; Malhotra, Anita; Mehra, Reeti; Kaur, Navjot (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of the study was to assess vascular function in normal pregnant women and women with gestational diabetes and to study its temporal relationship with gestational age at 24-28-week POG and at 36-38-week POG and changes in FMD in postpartum period. Methods: Assessment of vascular function was done at 24-28-week POG, 36-38-week POG and at 6-12-week postpartum by flow mediated dilation of brachial artery in 37 healthy pregnant women and 37 pregnant women with GDM. Results: In GDM group mean FMD at 24-28 weeks of POG, at 36-38 weeks POG was lower as compared to the control group (11.225±6.20,8.464±6.09 versus 14.49±5.21, 10.898±4.12) although the difference in mean FMD in two groups was not statistically significant. It was found that the decrease in FMD at 36-38-week POG as compared to 24-28 weeks POG was statistically significant in both the groups (p<0.001). Conclusions: This study revealed that when endothelial function as assessed by FMD was compared at different period of gestation, the mean decrease in FMD at 36-38-week POG as compared to 24-28-week POG and 6-week post-partum was statistically significant in patients with GDM and as well as the control group, however this trend of change was same in both the groups and was not statistically significant when compared between the two group (GDM versus control). A negative correlation of FMD was found with BMI, and HBA1c, that was stronger in GDM group.